ANALISIS EKO-EFISIENSI PADA USAHA KECIL DAN MENENGAH (UKM) BATIK TULIS BAKARAN (STUDI KASUS PADA BATIK TJOKRO) - Rifa'atussa'adah Rifa'atussa'adah; Bulan Prabawani (Universitas Diponegoro, 2017)
Eco-Efficiency is an efficiency concept that incorporates aspects of natural resources and energy or a production that minimizes the use of raw materials, water, energy and environmental impacts per unit of product. This study itself aims to determine the application of eco-efficiency in small and medium enterprises (UKM) batik tulis bakaran, precisely on Tjokro batik tulis. The type of research used is case study, model analysis using descriptive analysis with qualitative approach. Data collection using oral interviews, observation (observation), eco-efficiency measurement, and literature study. Based on the analysis once per production that is 30 pieces per day can be obtained, the total cost of NPO is Rp 519.579,64 per day or per 30 pieces of batik cloth. According to the data, there are 20 SME Batik Bakaran with total production volume of 3,821 sheets, resulting in NPO cost of Rp 66.177.121,72 per month. Suggestions for SMEs Batik Tulis Tjokro in terms of eco-efficiency is the use of raw materials in the production process should pass precise and thorough measurements, it is done so that not a lot of raw materials are wasted, and produce the cost of NPO (Non Product Output) the minimum.